2021
DOI: 10.1038/s41586-021-03889-2
|View full text |Cite
|
Sign up to set email alerts
|

Environmental performance of blue foods

Abstract: Fish and other aquatic foods (blue foods) present an opportunity for more sustainable diets 1,2 . Yet comprehensive comparison has been limited due to sparse inclusion of blue foods in environmental impact studies 3,4 relative to the vast diversity of production 5 . Here we provide standardized estimates of greenhouse gas, nitrogen, phosphorus, freshwater and land stressors for species groups covering nearly three quarters of global production. We find that across all blue foods, farmed bivalves and seaweeds g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
177
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 318 publications
(250 citation statements)
references
References 59 publications
(74 reference statements)
0
177
0
Order By: Relevance
“…It is critical to consider where and how aquatic foods are produced, because environmental, social and economic impacts can vary widely across both the wild-capture and aquaculture sectors (Supplementary Methods). Despite the variability in environmental impacts across animal-source food-production sectors, aquaculture and wild-capture fisheries nearly always produce fewer greenhouse gas emissions and use less land than the farming of red meats, and many AASFs outperform poultry 33 . Sustainably and equitably achieving the human health benefits of expanded aquatic food production will require policies and technologies that mitigate impacts on adjacent ecosystems, industries and communities 21 .…”
Section: Discussionmentioning
confidence: 99%
“…It is critical to consider where and how aquatic foods are produced, because environmental, social and economic impacts can vary widely across both the wild-capture and aquaculture sectors (Supplementary Methods). Despite the variability in environmental impacts across animal-source food-production sectors, aquaculture and wild-capture fisheries nearly always produce fewer greenhouse gas emissions and use less land than the farming of red meats, and many AASFs outperform poultry 33 . Sustainably and equitably achieving the human health benefits of expanded aquatic food production will require policies and technologies that mitigate impacts on adjacent ecosystems, industries and communities 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Chilean consumers have not yet demonstrated a strong preference for farmed salmon despite large-scale domestic production 70 . National health and environmental consequences of shifting diets from fish to terrestrial meats 60 , in addition to the environmental implications of expanding intensive salmon aquaculture to meet rising international demand 71 , illustrate the influence of global markets on nutrition and sustainability outcomes in countries like Chile that are significantly engaged in blue food trade.…”
Section: Demersal Fishmentioning
confidence: 99%
“…Aquaculture has become progressively more sustainable over the past 20 years, yet environmental challenges persist 18 . As aquaculture intensifies in both freshwater and marine systems, feed formulations will depend increasingly on terrestrial crop production and will continue to rely on marine resources 18,71 . Bivalves are widely advocated as a sustainable seafood option, but it is unclear how dietary preferences will evolve for this group of species.…”
Section: Demersal Fishmentioning
confidence: 99%
“…An assessment of aquatic foods with low negative impacts (called blue foods) by Gephart et al ( 2021 ) identified farmed, bivalve molluscs and seaweed as the most environmentally benign sources. They also found silver and bighead carps to have the lowest GHG potential, but production of these finfish required considerable land and water.…”
Section: Discussionmentioning
confidence: 99%
“…The changing climatic conditions are expected to worsen in years to come, and this challenge provides opportunity to create new systems of food production and to abandon or lessen the use of some systems in efforts to conserve land, water, and energy as well as to reduce greenhouse gas emissions (GHGs) or increase carbon sequestration (Campbell et al, 2016 ; Gephart et al, 2021 ; Rosenzweig et al, 2021 ; Thiault et al, 2019 ). This is important because food production uses 38% of land (FAO, 2016 ) and 70% of freshwater (FAO, 2016 ), while resulting in 25–35% of global greenhouse gas emission (IPCC, 2013 ; Tubiello et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%